Pengaruh Intensitas Moral Terhadap Etika Pengambilan Keputusan Pengguna Sistem Informasi - Prakosa, Fajar (Sekolah Tinggi Ilmu Manajemen dan Ilmu Komputer ESQ (STIMIK ESQ), 2017)
This research is aimed to analyze the influence of the moral intensity and personality toward to ethical decision-making of information systems users. Ethical decision-making variables measured by perceived ethical problem and behavioral intentions. The results of this study indicate that there is a relationship between moral intensity with ethical decision making that consists of perceived ethical problems and behavioral intention. The decision process is influenced by perceptions of individual circumstances, so as to provide evidence that supports the importance of the relationship between the intensity of moral and ethical decision making.